PENGARUH PEMBERIAN LUMPUR BUANGAN DARI PENGOLAHAN LIMBAH SINTESIS ANTIBIOTIKA DAN PUPUK KANDANG TERHADAP PERTUMBUHAN DAN PRODUKSI STEVIA (Stevia rebaudiana BERTONI M.) - Slamet Susanto; Muhammad Syukur (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1999)
The objective of the research was to investigate the effect of sewage application on growth and production of stevia, a sweetening alternative producing plant, as compared with manure application. Sewage is a by product of antibiotics processing of PT SBFI Sewage and manure application each consisted of 4 level, i.e. 0.0, 0.5, 1.0 and 1.5 kg per polybag. Sewage application has resulted in significant increase in tree high, leaf number, shoot number and root and shoot dry weight as compared with control. Manure application has resulted in significant increase in growth and production as compared with control. There was no interaction between sewage and manure application on all parameter observed